MIRERC 042/2025: Women, Peace and Security Agenda and Male Allyship - Alex Maxwell; Mutwiri, Antony; Susanna Campbell (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Executive Summary The WPS is an agenda that was initially underpinned by transformative feminist goals for gender equality. These underpinnings are being challenged by a shift in Global North politics where increased conservative, far-right populist and authoritarian governments, largely linked to an anti-gender agenda are exploiting the mobilising potential of misogyny. The shifting politics is resulting in increased military spending and a militant rhetoric in a project of ‘masculine restoration’ (Kandiyoti, 2019). In addition, shrinking civic spaces, Sweden’s shift from feminist foreign policy to ‘ traditional Swedish values’ (an important development actor signifying backsliding on gender equality focus), and a global decline in peacebuilding funding are significantly limiting progress made on gender equality. The WPS however continues to be mainstreamed by donors to tackle gender inequality despite the increasingly regressive everyday politics in multilateral/donor spaces. In view of the challenges outlined, this project seeks to investigate differences in how men and women promote WPS and gender equality, better understanding how the agenda is translated through the prism of male allyship. The research broadly asks: How do male allies make meaning of their promotion of women’s rights, through the WPS for example, in a context of increasing retrenchment of these rights? Taking an interpretive approach, the research will analyse how the WPS is interpreted by male advocates and community members in an urban settlement in Nairobi, Kenya. The research more broadly navigates the contradictions between delivering WPS goals while operating in a context where there is a backsliding on women’s rights and a more general retrenchment on gender equality in the West.